The perceived value on consumers’ experience when incorporating evidence based design in a vegan restaurant. - Gardner, Lara (The IIE, 2022)
This research report looked at the perceived value on consumers’ experience when incorporating evidence-based design in a vegan restaurant. Thus, the research problem would be to envision how to incorporate EBD, focusing on biophilia, colour psychology, indoor environmental quality, biomimicry as well as vegan interior design and vegan materials, into a vegan restaurant that will have a perceived value on consumers’ experiences. To solve this problem, research was conducted by looking into the value of EBD mainly focusing on biophilia, colour psychology, indoor environmental quality, and biomimicry, as well as doing interviews with the population identified and researching precedents on vegan restaurants that provide what vegan people like, not only in their food but also in the restaurant design. Thus, through the theories discussed and researched in this study, as well as the data collected, the research determined that evidence-based design looking at biophilia, colour psychology, and indoor environmental quality plays a critical role in the hospitality industry focusing on vegan restaurants. The perceived value on customer experience is imperative in a vegan restaurant setting. Therefore, by using evidence-based design and vegan materials the experience in the vegan restaurant setting is enhanced. Through the research, other designers will also see the value and positive impact that evidence-based design and vegan materials within a vegan restaurant using vegan interior design have, and that it is important and should be utilized in future designs of vegan restaurants. The contribution to the body of knowledge, current and future interior designers, as well as vegan restaurant owners; the research of the perceived value on consumers’ experience the incorporation of evidence-based design in a vegan restaurant will have, is that it will enable designers and business owners to realise the effectiveness of certain types of evidence based designs, such as the utilisation of specific colour psychology, indoor environmental quality and biophilia, and vegan interior design and materials, as well as the roles that designing vegan restaurants utilising EBD and vegan interior design will play on the profitability of the restaurant.
Keywords: Restaurants; Customer experience; Interior design; Biophilia; Colour